Effect of SKT 1 meditation therapy with music listening in the emergency room on blood pressure among hypertensive urgency patients - Phatarajittranon, Saisamorn; Nokham, Ranchana; Yoopu, Kanokpin (Journal of Medicine and Health Sciences, 2023)
Hypertensive urgency is another clinical emergency that leads patients to be admitted to the emergency room (ER). The study was a two-group quasi-experiment comparing pre- and post-tests with repeated measures. The objective was to examine the effects of Somporn Kantharadussadee Triumchaisri 1 or SKT 1 meditation and music listening in the emergency room on reducing blood pressure in patients with hypertensive urgency. The sample of 52 individuals was selected purposively and divided into an experimental group receiving SKT 1 meditation therapy with music listening and routine medical treatment, and a control group receiving routine medical treatment. Data were analyzed using descriptive statistics and repeated measures ANOVA. The results indicated that after the experiment, at 30 minutes, 60 minutes, and upon discharge, the experimental group showed statistically significant reductions in systolic and diastolic blood pressure compared to before the experiment (p<0.001). When comparing the mean blood pressure between the experimental and control groups after the experiment, at 30 minutes, 60 minutes, and upon discharge, it was found that the mean systolic blood pressure in the experimental group was significantly lower than the control group (p=0.011, p<0.001, p<0.001 respectively) and the mean diastolic blood pressure in the experimental group was significantly lower than the control group (p<0.001, p<0.001, p<0.001 respectively). The experimental group exhibited larger mean differences in blood pressure reduction compared to the control group at every time point. Therefore, it can be concluded that SKT 1 meditation therapy with music listening in the emergency room can reduce blood pressure in patients with hypertensive urgency. However, the study has limitations, and further research is necessary, particularly in larger sample groups, controlling for confounding variables, and conducting long-term studies.